Stakeholders' perspectives related to the development of a scooter training program. (18th May 2016) - Mortenson, W. Ben; Hoag, Emily; Higgins, Rosemary; Emery, Richelle; Joyce, Linda
Abstract: Purpose : To understand the perspectives of various stakeholders on the importance of and issues around scooter training and to identify elements recommended for a new scooter-training program. Methods : A cross-sectional survey was distributed to the past and present scooter users, their caregivers, scooter prescribers and vendors across Canada and internationally. These stakeholders were asked about the importance of scooter training, the training currently provided/available, and the content and format of training they preferred. Results : The majority of stakeholders strongly agreed that scooter training is important to ameliorate skills and increase confidence. Only 25% of scooter users reported receiving training. There was consensus regarding the basic (e.g. on/off switch, control, speeds, battery maintenance) and advanced skills (e.g. completing community errands, using an elevator, public transit, crossing intersections) that should be included in scooter training. Conclusion : Despite its perceived importance, few users reported receiving training, which suggests a large unmet need. The findings of this study lay the groundwork for the development of a scooter training program that is intended to give users the skills to participate safely and confidently in their communities. Implications for Rehabilitation: Respondents indicate that scooter training is important for skill development and self-confidence. Reported rates of scooter training are low. Respondents recommend that scooter training should occur in clients' homes and communities. Consideration of the person and their environment is important to ensure that training meets the needs and abilities of the scooter user.